Interorganizational collaboration in public health data sharing. Issue 6 (19th September 2016) - Casey, Colleen; Li, Jianling; Berry, Michele
Abstract : Purpose: The purpose of this paper is to analyze the institutional and social forces that influence collaborative data sharing practices in cross-sector interorganizational networks. The analysis focusses on the data sharing practices between professionals in the transportation and public health sectors, areas prioritized for collaborative action to improve public health. Design/methodology/approach: A mixed methods design is utilized. Electronic surveys were sent to 57 public health and 157 transportation professionals in a large major metropolitan area in the USA (response rate 39.7 percent). Focus groups were held with 12 organizational leaders representing professionals in both sectors. Findings: The application of the institutional-social capital framework suggests that professional specialization and organizational forces make it challenging for professionals to develop the cross-sector relationships necessary for cross-sector collaborative data sharing. Research limitations/implications: The findings suggest that developing the social relationships necessary for cross-sector collaboration may be resource intensive. Investments are necessary at the organizational level to overcome the professional divides that limit the development of cross-sector relationships critical for collaborative data sharing. The results are limited to the data sharing practices of professionals in one metropolitan area. Originality/value: Despite mandates and calls for increased cross-sector collaboration to improve public health, such efforts often fail to produce true collaboration. The study's value is that it adds to the theoretical conceptualization of collaboration and provides a deeper understanding as to why collaborative action remains difficult to achieve. Future study of collaboration must consider the interaction between professional specialization and the social relationships necessary for success.